Perang Enam Hari Arab Israel 1967 menerusi perspektif teori realisme - Mohd Irwan Syazli Saidin; Wan Kamal Mujani; Azyati Azhani Mohd Mazuki (Department of Theology and Philosophy, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2016)
Realism approach has dominated the studies of world politics and international relations since the last of the World War II and until the start of the Cold War era. The focus of this study is to look into the factors that ignited the war other than identifying the policies or actions taken by the countries involved in the war. The question that arises lies in the extent to which the approach is able to explain the factors and actions taken by the leaders, to the point that it led to the 1967 war, and how this war can serve as guidance for our understanding of the Realism Theory. The objective of this study is to unravel the chains of events that had become the background of the 1967 Arab-Israeli War by concentrating on the root causes of the war and the policies of the countries involved, other than offering justification for the Realism Theory by looking closely into the characteristics, assumptions, and concepts under this approach. The methodology of this work employs document analysis and historical studies to obtain complete data. The analysis was carried out by applying the Arab-Israeli war events to the Realism Theory to prove that there is an association between the causes of the war and the theory through the analysis unit, key assumptions and substantial concepts contained in the Realism approach. The unit of analysis, which places the countries as the main actor in the international system, can be seen through the main role of Egypt, Jordan, Syria and Israel throughout the period of war. Concepts such as power, power balance, national interests, national sovereignty and self-help are also associated with the causes behind this war through a series of facts that have manifested themselves in the event.